Discovery, synthesis and characterization of a series of 7-aryl-imidazo[1, 2-a]pyridine-3-ylquinolines as activin-like kinase (ALK) inhibitors. Issue 18 (15th September 2020) - Engers, Darren W.; Bollinger, Sean R.; Felts, Andrew S.; Vadukoot, Anish K.; Williams, Charles H.; Blobaum, Anna L.; Lindsley, Craig W.; Hong, Charles C.; Hopkins, Corey R.
Graphical abstract: Abstract: The activin-like kinases are a family of kinases that play important roles in a variety of disease states. Of this class of kinases, ALK2, has been shown by a gain-of-function to be the primary driver of the childhood skeletal disease fibrodysplasia ossificans progressiva (FOP) and more recently the pediatric cancer diffuse intrinsic pontine glioma (DIPG). Herein, we report our efforts to identify a novel imidazo[1, 2- a ]pyridine scaffold as potent inhibitors of ALK2 with good in vivo pharmacokinetic properties suitable for future animal studies.